2007
DOI: 10.1177/1464884907078659
|View full text |Cite
|
Sign up to set email alerts
|

The journalist, the housewife, the citizen and the press

Abstract: The use of sources in news narratives is an extremely important part of not only the story's construction but also of its orientation and, ultimately, the point of view being supported in a given story. The sly deceit concealed within journalists' use of sources as apparently independent and authoritative commentators enables the journalist to masquerade as a mere conveyance of others' perspectives while actually peddling a particular viewpoint by the choice of speaker and the choice of quote. This study inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 39 publications
1
44
0
11
Order By: Relevance
“…The representation of Irish women's engagement in politics is constituted through four dominant frames. Firstly, women are marginalised by literally being 'framed out' of the political picture (Ross & Carter, 2011), secondly, they are framed through a visual gendering of politicians which presents women in a limited manner (Lundell & Ekström, 2008), thirdly the source-frame is not applied equally to men and women on Prime Time (Ross, 2007) and finally, women are framed as participants only in a limited set of topics for discussion (Heldman et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The representation of Irish women's engagement in politics is constituted through four dominant frames. Firstly, women are marginalised by literally being 'framed out' of the political picture (Ross & Carter, 2011), secondly, they are framed through a visual gendering of politicians which presents women in a limited manner (Lundell & Ekström, 2008), thirdly the source-frame is not applied equally to men and women on Prime Time (Ross, 2007) and finally, women are framed as participants only in a limited set of topics for discussion (Heldman et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Scharrer (2002) found that in newspaper reports, the more Hilary Clinton was framed as politically active and more certain to run for office, the more the tone of the story was negative. Men are more likely to be presented as expert sources (Armstrong, 2004;Ross, 2007) and so their views are presented as more important and legitimate (Kim & Weaver, 2003). As Ross puts it 'If what we see and read and hear are men's voices, men's perspectives, men's news (then) women continue to be framed as passive observers rather than active citizens ' (2011: 19).…”
Section: Women Politics and Media Frameworldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of women as sources, compared to men, is one of the chief aspects for determin ing the image of women created by the media, more so than their presence as such. There is a considerable volume of academic literature devoted to this issue 5 : Ross (2007) and Armstrong (2004 and. As Gans states, journalists choose their sources precisely for their suitability, credibility and relevance.…”
Section: Introduction Literature Reviewmentioning
confidence: 99%
“…However, some studies argue that "news is news and the journalist's gender does not influence the selection criteria Lavie and LehmanWilzig (2003) 7 , while oth ers, such as Ross (2007), and Rodgers and Thorson (2003) 8 clearly show that at least when the problems concern women, then the approaches may be tackled in very dif ferent ways. For example, the study carried out by Altés, Gallego, Bach et al (2000) on the follow up of information on the Beijing Conference in 1995, showed that un questionably, the approaches varied according to whether the reports were written by men or women.…”
Section: Introduction Literature Reviewmentioning
confidence: 99%